Electronic and Optical Properties of Small Metal Fluoride Clusters - Cappellini, Giancarlo; Bosin, Andrea; Serra, Giovanni; Furthmueller, Juergen; Bechstedt, Friedhelm; Botti, Silvana (ACS Omega, 2020)
We report a systematic investigation on the electronic and optical properties of the smallest stable clusters of alkaline-earth metal fluorides, namely, MgF2, CaF2, SrF2, and BaF2. For these clusters, we perform density functional theory (DFT) and time-dependent DFT (TDDFT) calculations with a localized Gaussian basis set. For each molecule ((MF2)n, n = 1-3, M = Mg, Ca, Sr, Ba), we determine a series of molecular properties, namely, ground-state energies, fragmentation energies, electron affinities, ionization energies, fundamental energy gaps, optical absorption spectra, and exciton binding energies. We compare electronic and optical properties between clusters of different sizes with the same metal atom and between clusters of the same size with different metal atoms. From this analysis, it turns out that MgF2 clusters have distinguished ground-state and excited-state properties with respect to the other fluoride molecules. Sizeable reductions of the optical onset energies and a consistent increase of excitonic effects are observed for all clusters under study with respect to the corresponding bulk systems. Possible consequences of the present results are discussed with respect to applied and fundamental research.
CRIS-Team Scopus Importer:2023-04-20